PENILAIAN AGUNAN DALAM KEPUTUSAN PEMBERIAN PEMBIAYAAN DI BMT MANDIRI UKHUWAH PERSADA SURABAYA - Abdullah Ahadish Shamad Muis; Lailatul Mukarromah (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2021)
The purpose of this study was to determine the financing procedures and collateral valuation in the decision to provide financing at BMT Mandiri Ukhuwah Persada Surabaya. The approach used in this research is descriptive qualitative. The data sources used are primary and secondary data. Namely from the results of interviews, observations, and several documents that can answer the formulation of the problem in this study. Then, the data analysis technique used is content analysis. Based on the data analysis carried out, it was found that the procedure for providing financing at BMT Mandiri Ukhuwah Persada was the same as that for financial institutions in general. The process or stages that BMT Mandiri Ukhuwah Persada members must go through to apply for financing are first registering to become members, preparing the required files, and other processes. There are two types of collateral at BMT Mandiri Ukhuwah Persada. First, material collateral, namely in the form of ID cards, marriage books, family cards, motor vehicle ownership book (BPKP), house/land certificates, and deposit savings. Second, non-material collateral, where members can apply for financing with collateral in the form of personal guarantees, which is termed gandeng renteng. The valuation of material collateral at BMT Mandiri Ukhuwah Persada is considered to be less specific, because it does not have a clear percentage standard. However, for the assessment of non-material collateral, BMT Mandiri Ukhuwah assesses the nature of the trust, and the activeness of the members in transactions.